Предмет: Алгебра,
автор: serjanskao29
Срочьно!!!!! Поможіть!!!!
Приложения:
Ответы
Автор ответа:
1
Ответ:
ну по сути должно быть вот так
продолжение второго
х³-х²+х²+1-2
------------------ =
(х-1)•(х²+х+1)
х³-1
= ------------------ =
(х-1)•(х²+х+1)
(х-1)•(х²+х+1)
= ----------------- =1
(х-1)•(х²+х+1)
Приложения:
Похожие вопросы
Предмет: Химия,
автор: olecjamtrubach
Предмет: Другие предметы,
автор: kinzhibaevs31
Предмет: Биология,
автор: sabinamletsko
Предмет: Биология,
автор: dimshahov2011
Предмет: Алгебра,
автор: lite123df